Wide occurrence of seven phthalate plasticizers and two typical microplastics in pig feed. (November 2022) - Xu, Jiaping; Bi, Wanjuan; Hua, Liting; Cheng, Zhipeng; Wang, Yu; Li, Dandan; Liu, Weitao; Wang, Lei; Sun, Hongwen
Abstract: Plastics are widely used as packaging and engineering materials in feed processing, which leads to the potential contamination of plasticizers and microplastics (MPs) in animal feeds. In this study, the concentrations of two typical MPs, i.e., polyethylene terephthalate (PET) and polycarbonate (PC), and seven phthalates (PAEs) as well as their corresponding monoester metabolites (mPAEs) in 45 pig feed samples in China were analyzed by mass spectrometers. Among PAEs, dibutyl phthalate (DBP) and bis(2-ethylhexyl) phthalate (DEHP) were detected in all samples, and DEHP showed the highest concentrations of 8.26–2464 μg/kg, which accounted for 65.6% of the total detected PAEs. PET MPs (<MDL-302 μg/kg) were detected in 97.8% of samples. Meanwhile, mPAEs were also detected in feed samples with high detection rates but of much lower concentrations. A significantly positive correlation was observed between DEHP and PET MPs. This indicates that the sources of DEHP and MPs in feeds are homologous, mainly from processing and packaging. Besides, the significantly positive correlations between DBP/DEHP and mBP/mEHP indicated the degradation of PAEs to mPAEs during feed production and transportation. The estimated daily intake (EDI) of PAEs and PET MPs were 2.40–70.3 and 0.800–7.79 μg/kg-bw-day, respectively. The results of this study provided new insight into the first evidence of the co-occurrence and risk of MPs, PAE, and mPAEs in pig feed. Graphical abstract: Image 1 Highlights: PET MPs were extensively detected by mass spectrometry in pig feed with the concentration of < MDLs - 302 μg/kg. The co-occurrence of phthalates and monoester metabolites was reported for the first time in pig feed. Significant associations between DEHP -PET and DBP/DEHP- their monoesters were observed.